2020
DOI: 10.1186/s12883-020-01682-8
|View full text |Cite
|
Sign up to set email alerts
|

A ruptured posterior communicating artery aneurysm presenting as tentorial and spinal isolated subdural hemorrhage: a case report and literature review

Abstract: Background: Ruptured intracranial aneurysms are often associated with subarachnoid or intraparenchymal hemorrhage. However, the prevalence of subdural hemorrhage post aneurysmal rupture is low and rarely reported in scientific studies. Here, we report an unusual case of a ruptured posterior communicating artery aneurysm resulting in an isolated subdural hematoma located in the tentorial and spinal canal without subarachnoid or intraparenchymal hemorrhage. Case presentation: In this case, a 34-year-old woman wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…[4] Others in the past have estimated the incidence of mixed AnSDH/SAH to be anywhere from 0.5% to 7.9%. [1] e incidence of isolated AnSDH is certainly much lower and only represented in the literature in case reports and small case series PcomA location is a recurrent theme among risk factors for developing SDH following aneurysmal rupture. [2] Hypotheses for SDH formation Multiple hypotheses have been proposed but the most common involves the formation of adhesions between the aneurysmal wall, arachnoid membrane, and dura.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[4] Others in the past have estimated the incidence of mixed AnSDH/SAH to be anywhere from 0.5% to 7.9%. [1] e incidence of isolated AnSDH is certainly much lower and only represented in the literature in case reports and small case series PcomA location is a recurrent theme among risk factors for developing SDH following aneurysmal rupture. [2] Hypotheses for SDH formation Multiple hypotheses have been proposed but the most common involves the formation of adhesions between the aneurysmal wall, arachnoid membrane, and dura.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Only three studies were identified that met the inclusion criteria of having an aSDH involving the infratentorial fossa with no associated SAH [ Figure 1 ]. [ 1 , 5 , 6 ] The age, sex, race, comorbidities, hematoma location, radiographic data, clinical presentation, medical and surgical management, complications, and outcomes were analyzed and are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations